Scientific writing with artificial intelligence: key considerations and alerts - Gonçalves, Sergio Eduardo de Paiva [UNESP]; Tribst, João Paulo Mendes; Fardim, Karolina Aparecida Castilho [UNESP] (Editora Cubo, 2023)
The integration of artificial intelligence (AI) text generators in scientific reports demands careful evaluation of specific ethical considerations. While these AI technologies offer text generation support, addressing the ethical implications is vital. This editorial highlights the need for a thoughtful and responsible approach, emphasizing the establishment of guidelines and best practices by researchers and scientific communities. Collaborative efforts between AI developers, researchers, and ethical committees can ensure the seamless integration of AI technologies while upholding the integrity, quality, and ethical standards of scientific reporting. This text comprehensively summarizes the key considerations to be followed when utilizing artificial intelligence text generators in scientific reports.
Escrita científica com inteligência artificial: principais considerações e alertas
Keywords: Artificial intelligence; Dental society; Ethics; Forecasting; Scientific society